HYDRODYNAMIC MIXER OPERATION BY BIODIESEL PRODUCTION FROM JATROPHA OIL - Hoang Nghia Dat; G. G. Parkhomenko; V. I. Pakhomov; V. B. Rykov; S. I. Byr’Ko; I. V. Bozhko (Сельскохозяйственные машины и технологии)
A process of functioning of the hydrodynamic mixer which mixes streams of biodiesel fuel from Jatrofa oil of the increased acidity with carbon dioxide for its washing was considered. The regularities revealing interrelation of parameters (diameter and length of the mixing camera), the modes (pressure and stream speed) with properties of the environment (dynamic viscosity, density, elasticity) and power indicators of process (intermixing capacity) was obtained. On the basis of a method of similarity and dimensions of physical quantities criterion of stream turbulence was received, modes were determinate, diameter of the mixing camera (30-35 mm) was recommended. Stream pressure decrease and intermixing capacity at increase in pipeline diameter were established. When diameter is more than 30 mm, so pressure intensity modification is the smallest and dependence become like linear function. The intermixing capacity increases most intensively (by 1.5 times) with reduction of mixing camera length from 15 to 10 mm and it ceases to decrease at 30-35 mm. When pressure on a cut of a nozzle corresponds critical, carbon dioxide in the mixing camera gets liquid properties, dissolving in biofuel, and mix becomes quasihomogeneous. The revealed criterion of stream change modes from supersonic in the subsonic allowed to define a condition of quasiuniformity of mix. It was proved that the supersonic stream formed thus «liquid-gas» is transformed in subsonic, accompanied at acoustic effect of cavitation with a intermixing due to isentropic jump in pressure. There were proved physical and chemical data of process of cavitational impact of carbon dioxide on biodiesel fuel as a result of which properties of the environment improve owing to structurization of molecules of solution that positively influences mixing. A design of the hydrodynamic mixer was recommend.